2016
DOI: 10.18632/oncotarget.9241
|View full text |Cite
|
Sign up to set email alerts
|

The IRX1/HOXA connection: insights into a novel t(4;11)- specific cancer mechanism

Abstract: One hallmark of MLL-r leukemia is the highly specific gene expression signature indicative for commonly deregulated target genes. An usual read-out for this transcriptional deregulation is the HOXA gene cluster, where upregulated HOXA genes are detected in MLL-r AML and ALL patients. In case of t(4;11) leukemia, this simple picture becomes challenged, because these patients separate into HOXA hi -and HOXA lo -patients. HOXA lo -patients showed a reduced HOXA gene transcription, but instead overexpressed the ho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
33
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 27 publications
(36 citation statements)
references
References 48 publications
1
33
0
2
Order By: Relevance
“…To investigate if the presence of RAS mutated clones was associated with a distinct leukaemia transcriptional profile, fifteen samples (n = 4 RAS wt and n = 11 RAS mut ) with available gene expression data were analysed. We first examined the expression levels of HOXA9, HOXA10 and IRX1 genes that were previously shown to discriminate within MLL-AF4 leukaemia two distinct signatures 24 25 26 , Fig. 3A .…”
Section: Resultsmentioning
confidence: 99%
“…To investigate if the presence of RAS mutated clones was associated with a distinct leukaemia transcriptional profile, fifteen samples (n = 4 RAS wt and n = 11 RAS mut ) with available gene expression data were analysed. We first examined the expression levels of HOXA9, HOXA10 and IRX1 genes that were previously shown to discriminate within MLL-AF4 leukaemia two distinct signatures 24 25 26 , Fig. 3A .…”
Section: Resultsmentioning
confidence: 99%
“…Of note, a recent study showed that approximately half of t(4;11) + patients do not have an activated HOXA signature. 44,53,54 Furthermore, in the recent MLL-Af4-induced B-ALL xenograft model MLL-Af4 failed to bind to HOXA genes and therefore HOXA gene expression was not upregulated. 21 This is experimentally supported by chromatin immunoprecipitation-sequencing analysis performed in human embryonic stem cells transduced with MLL-AF4, AF4-MLL or both showing a significant enrichment of H3K79 methylated regions specifically associated with HOX-A cluster genes in double fusion-expressing hematopoietic derivatives, establishing a functional and molecular cooperation between MLL-AF4 and AF4-MLL fusions during human hematopoietic development ( data not shown ).…”
Section: Discussionmentioning
confidence: 99%
“…This is in line with the recently found significant positive correlation between the upregulation of the HOX-A gene cluster and the expression of A4M in primary t(4;11) + infant B-cell ALL samples, and with previous studies identifying that approximately one-half of t(4;11) + patients do not have an activated HOX-A signature. 20,65,66 This may explain why MA4 failed recently to bind to HOX-A genes to regulate HOXA gene expression. 14 Collectively, MA4 and A4M might cooperate through a complex molecular interaction to control HOX-A gene regulation.…”
Section: Discussionmentioning
confidence: 99%